Socio-Cultural Nutrition Analysis in Jatisura Village, Indramayu Regency, West Java, Indonesia - Nur Intania Sofianita; Ibnu Malkan Bakhrul Ilmi; Utami Wahyuningsih; Iin Fatmawati; Widayani Wahyuningtyas (Journal of Global Nutrition, 2025)
Jatisura Village is located in Cikedung District, Indramayu Regency. Most of the residents earn a living as agricultural workers. The village boasts various tourism opportunities, such as Situ Bolang Agrotourism, which serves to retain water for irrigating the fields of local farmers and can also yield freshwater fish that can be consumed or transformed into products for Micro, Small, and Medium Enterprises. The aim of the research is to assess the socio-cultural nutrition aspects, including economic conditions, educational levels, knowledge, and the nutritional status of school-aged children and adolescents in Jatisura Village. Method: mixed method approach. incorporating both qualitative explorative and quantitative techniques. A total of 12 participants were involved, including village officials, integrated health post cadres, adolescents, community leaders, traditional leaders, village midwives, and representatives from Islamic elementary and high schools. For the quantitative portion, purposive sampling was applied, comprising 18 health cadres, 32 adolescents from high schools, and 60 children from elementary schools. This study was carried out between September 2022 and March 2023. Results: The majority (90.1%) of residents in the village earn incomes below the Minimum Wage set by Indramayu Regency. Jatisura Village is home to Micro, Small, and Medium Enterprises that have the capacity to export their products internationally, such as Rolisa Food, which produces mango crackers, mango seed coffee, mango preserves, mango juice, orange leaf nuts, and cow skin crackers. The understanding of nutrition among less than 33% of community leaders, 28.1% of teenagers, and 88.7% of school-age children is limited. In terms of nutritional status, 28.2% of teenagers are classified as underweight, and 16.7% of elementary school children show signs of stunting. Conclusion: The tourism opportunities in Jatisura Village can be enhanced by utilizing local food resources to create distinctive souvenirs, thereby boosting the income of the villagers. There are still adolescents experiencing inadequate nutritional levels and elementary school children facing stunting issues related to nutrition. It is essential to offer nutrition education and healthy food management training to the villagers to elevate their purchasing power for nutritious food and enhance education and health for the entire community.